Surgical management for MEN 2 syndromes - Biczysko, Maciej; Drews, Michał; Stawny, Bolesław (Contemporary Oncology/Współczesna Onkologia, 2005)
MEN-2 syndromes belong to a small number of well documented inherited neoplasms. Mutations in different codons of the RET proto-oncogene are responsible for clinical appearance and penetrance of the disease. The last decade brought numerous important scientific discoveries precisely identifying codons, mutations and their clinical significance. In relation with genetical and basic science progress there is a constant improvement of clinical management of these syndromes. Due to precise early diagnosis in an asymptomatic patient it is possible to perform prophylactic surgical procedures. An increasing number of clinical and genetical observations impact the type and especially the timing of surgery. Codon involvement influences the strongest type of the syndrome and surgery timing. The paper discusses classification, diagnostic procedures and treatment in symptomatic and asymptomatic patients. A particular stress was put on prophylactic surgical treatment for a risk of preinvasive medullary thyroid carcinoma, promising patients best chances for cure. Adrenal surgery problems are discussed, particularly the laparoscopic approach to these organs and modern cortical tissue sparing techniques. There is also constant progress in primary hyperparathyroidism treatment, accompanying MEN 2 syndromes. We discuss pros and cons of different types of parathyroid surgical techniques and their clinical impact on the final outcome. Total parathyroid removal and autotransplantation are also discussed.